Exploration of the High‐Capacity Tetrahydroxybenzene Materials for Organic Batteries - Klemen Pirnat; Uroš Javornik; Nerea Casado; Nicholas Ballard; Jose Ignacio Santos; David Mecerreyes; Robert Dominko (ChemElectroChem)
Abstract Polyphenol or multihydroxybenzene compounds show great potential as electrode material for organic batteries. Among them, 1,2,3,4‐tetrahydroxybenezene is the best candidate as a high‐specific capacity material due to its potential to exchange up to four electrons. To further corroborate this, we synthesized a model compound and carry out electrochemical characterization. Quasi‐reversible redox behavior, similar to other hydroxybenzene materials, was obtained in an acidic aqueous electrolyte. The four electron exchange was further confirmed by using reduced and oxidized model compounds, which showed comparable electrochemical behavior. Additionally, we prepared insoluble nano sized polymer based on poly(2,3,4,5‐tetrahydroxystyrene) which was used as a cathode material in an organic battery. Initial results suggested that these tetrahyroxybenzene polymers are very promising for proton batteries in acidic aqueous electrolytes, whereas their performance in lithium batteries is limited.